2017
DOI: 10.1111/jvim.14783
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin‐Resistant Staphylococcus aureus from Equine Nasopharyngeal and Guttural Pouch Wash Samples

Abstract: BackgroundMethicillin‐resistant Staphylococcus aureus (MRSA) is recognized as a cause of nosocomial infections in both human and veterinary medicine. Studies that examine the nasopharynx and guttural pouches of the horse as carriage sites for MRSA have not been reported.Hypothesis/Objective MRSA colonizes the nasopharynx and guttural pouch of horses. To determine the prevalence of MRSA in equine nasopharyngeal wash (NPW) and guttural pouch lavage (GPL) samples in a field population of horses.SamplesOne hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Samples were barcoded and PCR primers were used under the conditions described above. The software Quantitative Insights Into Microbial Ecology‐2 (QIIME2; https://qiime2.org) was used for sequence processing and analysis . The raw sequence data were de‐multiplexed, and low‐quality reads were filtered using database’s default parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were barcoded and PCR primers were used under the conditions described above. The software Quantitative Insights Into Microbial Ecology‐2 (QIIME2; https://qiime2.org) was used for sequence processing and analysis . The raw sequence data were de‐multiplexed, and low‐quality reads were filtered using database’s default parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Although the MRSA prevalence in horses in Switzerland in 2020 was likely due to a small outbreak in one region, this study provided insights into MRSA carriage in healthy horses in Switzerland. As observed in other countries, the MRSA carriage prevalence in the healthy horse community tends to be usually lower (<0,53 % to 4 %) 6,7,28,31,58 compared to the reported prevalence in horses at hospital admission and in hospitalized horses, which ranges between 1,9 % to 16,4 %. 42,50,51,60,61,67 Similarly to our study, regional dissemination has already been shown to be responsible for increase in prevalence, but such prevalence would decrease when considered on a nationwide scale.…”
Section: Discussionmentioning
confidence: 54%
“…Nebulized amikacin (1750 mg in 21 mL total volume) or nebulized enrofloxacin (175 mg in 10 mL total volume) has begun to be used in horses that are continuously colonizing LA-MRSA with shown success in eradicating LA-MRSA colonization [113]. In addition, antibiotic nebulation is not appropriate in cases of LA-MRSA colonization that occurs in the gastrointestinal tract and guttural pockets in horses [114]. Therefore, the efficacy and safety of nebulized antibiotics still require further research.…”
Section: Treatment Of La-mrsa Infection In the Horsementioning
confidence: 99%